Design of 1.55 um InGaAsNBi/GaAs quantum well laser - Kwan, Zi Jian (2017)
The use of InGaAs/GaAs quantum well (QW) lasers has started to become prevalent in fiber communications. It is found that by operating at 1.55um minimal optical loss can be achieved. Bismide has been added so as to achieve the ideal 1.55um wavelength for the QW laser. Simulations with varying bismide compositions have been run so as to find which bismide composition would achieve the desired 1.55um wavelength. A graph depicting the relationship between various QW widths (WW) versus the bandgap energy has been plotted.